Impact of Groundwater Table Fluctuations on the Bearing Capacity of Shallow Foundations in Sandy Soils: A Parametric Analysis Using PLAXIS 3D Modeling - Manal Abmdas; Jadullah Al-Awamy (AlQalam Journal of Medical and Applied Sciences, 2025)
The critical influence of groundwater table (GWT) fluctuations on the bearing capacity of shallow foundations in sandy soils is examined in this study, a component sometimes undervalued in geotechnical design. Using sophisticated PLAXIS 3D numerical simulation, a thorough parametric analysis was done to evaluate how different GWT values affect the ultimate and allowed bearing capacities across a range of foundation sizes (1m x 1m to 4m x 4m) and embedment depths (0. 00m to 1. 50m). As the lower of the capacity based on a factor of safety (qu/3) and the settlement-limited capacity (S25mm), the allowable design bearing capacity (qall) was calculated. The results show a notable inverse correlation between foundation size and GWT sensitivity: smaller foundations (1m x 1m) had the most major reductions in bearing capacity (up to 45. 97% for surface foundations at GWT=0. 00m), whereas larger foundations (4m x 4m) showed more stability (maximum 7. 48% reduction under comparable conditions). Increased embedment depth helped to reduce these negative consequences throughout all foundation sizes. One of the most important results is that keeping a minimum of 1. 00 m between the groundwater table and the foundation base virtually removes the effects of groundwater. The study also underlines non-linear correlations in bearing capacity reductions, therefore indicating complicated soil-structure interactions. Emphasizing the need for thorough groundwater studies for structural safety and best performance, this study offers vital data and ideas for improving predictive models and producing superior design guidelines for shallow foundations in sandy soils.